THE EVOLUTION OF SALES ETHICS: ANALYSES OF THE PAST AND STRATEGIES FOR THE FUTURE - Zaenal Aripin; Finny Redjeki; Endang Ruchiyat (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
The evolution of ethics in sales practices has become an important subject in the increasingly complex and globally connected context of modern business. This research aims to analyze the development of ethics in sales from a historical perspective to future strategies. Through a literature study approach, this analysis identifies a significant shift from sales practices that focus solely on profits towards more ethical and sustainable practices. The first subchapter explains the evolution from the aggressive and less ethical sales practices of the past to the more transparent and responsible approach of today. The second subchapter highlights trends in modern sales ethics, including the increasing use of technology to increase transparency and personalization in company-consumer relationships. The third subchapter explores the implications of technology, especially artificial intelligence and data analysis, in improving a company's operational efficiency while maintaining high ethical values. The fourth subchapter formulates strategies for the future, including the development of a strict code of ethics, responsible technology implementation, and commitment to corporate social responsibility and sustainability. The conclusions of this research confirm that companies must adopt a holistic approach to ethics in sales to build a strong reputation and sustainable relationships with consumers and society. By integrating ethical values into their business strategies, companies can position themselves to better face future challenges while strengthening competitiveness in an increasingly complex global marketplace.